Electrophotocatalytic Undirected C−H Trifluoromethylations of (Het)Arenes. Issue 15 (19th February 2020) - Qiu, Youai; Scheremetjew, Alexej; Finger, Lars H.; Ackermann, Lutz
Abstract: Electrophotochemistry has enabled arene C−H trifluoromethylation with the Langlois reagent CF3 SO2 Na under mild reaction conditions. The merger of electrosynthesis and photoredox catalysis provided a chemical oxidant‐free approach for the generation of the CF3 radical. The electrophotochemistry was carried out in an operationally simple manner, setting the stage for challenging C−H trifluoromethylations of unactivated arenes and heteroarenes. The robust nature of the electrophotochemical manifold was reflected by a wide scope, including electron‐rich and electron‐deficient benzenes, as well as naturally occurring heteroarenes. Electrophotochemical C−H trifluoromethylation was further achieved in flow with a modular electro‐flow‐cell equipped with an in‐operando monitoring unit for on‐line flow‐NMR spectroscopy, providing support for the single electron transfer processes. Abstract : Cooperation : Electrophotochemical C−H trifluoromethylations of unbiased arenes were accomplished by the cooperative action of electricity and light under mild reaction conditions.